2015
DOI: 10.1038/jhg.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of joints and arteries: second report with novel NT5E mutations and expansion of the phenotype

Abstract: Calcification of joints and arteries (CALJA; MIM 211800) is an extremely rare mendelian disorder of isolated calcification that is characterized by late onset calcification of the extremity arteries and hand and foot joint capsules. Mutations of NT5E, encoding cluster of differentiation 73, have been implicated in CALJA. Here we report on a Chinese family with CALJA and novel compound heterozygous mutations (c.1360G>A (p.Gly454Arg) and c.1387C>T (p.Arg463X)) in NT5E. Our study represents the second report on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Hilaire et al [ 23 ] performed linkage analysis and showed that rare mutations in NT5E affect the arterial and joint calcifications due to loss of NT5E function. Zhang et al [ 24 ] also performed candidate gene analysis and showed the association between calcification of joints and arteries and another non-synonymous SNP in NT5E (p.Gly454Arg), which was far away from the binding site of substrate AMP but next to the lacked locus of shorter NT5E isoform known as CD73S [ 25 ].These results indicated that the mutations in NT5E would affect the enzymatic activity of NT5E and thus were associated with these traits. The objective of finding variants associated with these traits are different in between human (for health) and cattle (for breeding), but our results could contribute to the genetic understanding the effect of NT5E variants on both human and cattle nucleotide metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hilaire et al [ 23 ] performed linkage analysis and showed that rare mutations in NT5E affect the arterial and joint calcifications due to loss of NT5E function. Zhang et al [ 24 ] also performed candidate gene analysis and showed the association between calcification of joints and arteries and another non-synonymous SNP in NT5E (p.Gly454Arg), which was far away from the binding site of substrate AMP but next to the lacked locus of shorter NT5E isoform known as CD73S [ 25 ].These results indicated that the mutations in NT5E would affect the enzymatic activity of NT5E and thus were associated with these traits. The objective of finding variants associated with these traits are different in between human (for health) and cattle (for breeding), but our results could contribute to the genetic understanding the effect of NT5E variants on both human and cattle nucleotide metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Initially identified in nine individuals from three unrelated families in 2011, arterial calcification due to CD73 deficiency (ACDC) has been show to specifically target lower extremity arteries, as well as of the hand and foot joint capsules . Recently, a second report from an independent Chinese group expanded the clinical portrait of ACDC identifying novel NT5E loss‐of‐function mutations and showing that calcification could also occurred in upper extremity arteries . From a mechanistic point of view, CD73‐derived adenosine was show to repress the expression of tissue non‐specific alkaline phosphatase (TNAP), thereby maintaining a high inorganic pyrophosphate/phosphate (PPi/Pi) ratio to inhibit mineralization.…”
Section: Ectonucleotidases and Vascular Regulationmentioning
confidence: 99%
“…The cause of the disease is recently identified as a mutation in the 5′-nucleotidase Ecto ( NT5E ) gene that encodes the CD73 enzyme. [1] , [2] , [3] Inactivation of CD73 results in decreased extracellular adenosine and inorganic phosphate, and increased tissue-nonspecific alkaline phosphatase (TNAP) activity, inducing the formation of calcifications in the hands and lower extremities [2] . Left untreated, this buildup can lead to severe peripheral obstructive arterial disease and arthritis [1] .…”
Section: Background On Acdcmentioning
confidence: 99%